Sirtuins and neuronal DNA damage under experimental chronic cerebral hypoperfusion - O. Yu. Harmatina; Т. Yu. Voznesenska; N. H. Hrushka; О. А. Kondratska; А. H. Portnychenko (Zaporozhye State Medical University, 2019)
Chronic brain hypoperfusion (ChCH) is a risk factor for central nervous system (CNS) diseases, such as chronic brain ischemia, degenerative diseases, and others, in this connection, the study of its pathophysiological mechanisms is an actual problem. Objective. To investigate the relationship between SIRT1/SIRT3 expression and activity and damage of neuronal DNA in conditions of chronic cerebral hypoperfusion in mice. Маterials and methods. The experiments were carried out on male C57Bl mice (6 weeks old, weight 18-20 g), which underwent occlusion of left common carotid artery to model ChCH. On the background of ChCH nicotinamide (NAM, 200 mg/kg, 10 d, i.p.) and resveratrol (RV, 10 mg/kg, 10 d, i.p.) were used. All manipulations were carried out in anesthetized with ketamine (60 mg/kg, i.p.) mice. In 8 weeks, in mice brain tissues the features of neuronal DNA damage were studied by DNA comet assay and SIRT1/SIRT3 gene expression levels by real-time RT-PCR. Results. ChCH modeling was accompanied on the unilateral side by an increase of DNA damage (comets within classes 3 and 4) index of neurons by 6.9 times, and by a decrease of SIRT1 and SIRT3 gene expression by 9.3 and 20.2 times, respectively, compared to control (P < 0.05). Using of NAM and RV treatment resulted in reduction of DNA damage index by 89.6 % and by 92.4 %, respectively, compared to control (P < 0.05), and in the increase of the levels of SIRT1 by 1.7 and 3.5 times, and SIRT3 - by 2.9 and 5.2 times, respectively, in comparison with the ChCH group (P < 0.05). Conclusion. Taken together, these data indicate that modification of SIRT1 activity caused positive effect on ChCH-induced brain injury by attenuating DNA breaks, which was accompanied with up-regulation of SIRT-mediated regulatory pathways.